Role of thyroid hormones in apolipoprotein A-I gene expression in rat liver. - Strobl, W (1990)
To study the regulation of hepatic apo A-I gene expression, we measured synthesis and abundance of cellular apo A-I mRNA and its nuclear precursors in livers of hypothyroid and hyperthyroid rats. In hypothyroid animals, both synthesis and abundance of apo A-I mRNA was reduced to half of control values. After injection of a receptor-saturating dose of triiodothyronine into euthyroid rats, apo A-I gene transcription increased at 20 min, reached a maximum of 179% of control (P less than 0.01) at 3.5 h, and remained elevated for up to 48 h. The abundance of nuclear and total cellular apo A-I mRNA increased at 1 and 2 h, respectively, and exceeded the levels expected from enhanced transcription more than two fold at 24 h after hormone injection. Upon chronic administration of thyroid hormones, levels of nuclear and cytoplasmic apo A-I mRNA remained elevated but transcription of the apo A-I gene fell to 42% of control (P less than 0.01). Thus, thyroid hormones rapidly stimulate apo A-I gene transcription. Posttranscriptional events leading to increased stability of nuclear apo A-I RNA precursors become the principal mechanism for enhanced gene expression in chronic hyperthyroidism and may cause feedback inhibition of apo A-I gene transcription. Our results furthermore imply that the majority of hepatic nuclear apo A-I RNA precursors are degraded in euthyroid animals.